2015
DOI: 10.1186/2045-7022-5-s3-p57
|View full text |Cite
|
Sign up to set email alerts
|

Children's food allergy in Mexico

Abstract: MexiprevAAl is a prospective cross-sectional study carried out in 2000 patients recruited in outpatient clinics. Here we present results from pediatric population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Zhengzhou et al analyzed 1299 children from Henan province who were tested for food allergens, and identified eggs, milk, and cod as the main allergens [28]. In a Mexico study conducted in the year 2013–2014, the highest frequency of suspected allergic reactions was related to milk (44.5%), fruit (25.4%), eggs (21.8%), cereals (19.6%), and seafood (13.6%) [29]. Furthermore, James et al [3] examined 300 city students from the United States and identified peanuts and nuts as the major food allergens.…”
Section: Discussionmentioning
confidence: 99%
“…Zhengzhou et al analyzed 1299 children from Henan province who were tested for food allergens, and identified eggs, milk, and cod as the main allergens [28]. In a Mexico study conducted in the year 2013–2014, the highest frequency of suspected allergic reactions was related to milk (44.5%), fruit (25.4%), eggs (21.8%), cereals (19.6%), and seafood (13.6%) [29]. Furthermore, James et al [3] examined 300 city students from the United States and identified peanuts and nuts as the major food allergens.…”
Section: Discussionmentioning
confidence: 99%
“…Un estudio epidemiológico de varias regiones de México mostró que el asma podría coexistir hasta en 35 % de los sujetos con alergia alimentaria. 92 Sin embargo, solo en raras ocasiones (< 2 %) las reacciones alérgicas a alimentos serán disparadores de síntomas respiratorios o asma.…”
Section: Frecuenciaunclassified